2015
DOI: 10.11648/j.ajbio.20150302.14
|View full text |Cite
|
Sign up to set email alerts
|

Splenic Niche Cells from Young Heterochronic Parabionts Have Decreased Capability to Amplify T-cell Proliferation in Vitro

Abstract: Abstract:Immune system dysfunction during aging is well documented fact. Changes in the adaptive immune system are the most marked, especially in the T-cell compartment. In multiple preliminary studies it has been shown that parabiosis between 2 animals of different age can induce age-related changes in adaptive immune response and T-cell subpopulation composition of younger animal. In present study we evaluated the age-related changes in functions of rapidly renewing (macrophages) and slowly renewing cells (C… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 38 publications
0
5
0
Order By: Relevance
“…Also, during stimulation in vitro in the presence of autologous macrophages, T-cells from young heterochronic parabionts had a lower expression of NFκB p65 on early stages of stimulation (2 h) and a higher expression of IκBα on later stages (18 h) of stimulation when compared with T-cells from young isochronic parabionts. Observed data indicate the induction of negative changes in functions of macrophage-rich population of splenocytes during heterochronic parabiosis [33].…”
Section: Discussionmentioning
confidence: 90%
See 1 more Smart Citation
“…Also, during stimulation in vitro in the presence of autologous macrophages, T-cells from young heterochronic parabionts had a lower expression of NFκB p65 on early stages of stimulation (2 h) and a higher expression of IκBα on later stages (18 h) of stimulation when compared with T-cells from young isochronic parabionts. Observed data indicate the induction of negative changes in functions of macrophage-rich population of splenocytes during heterochronic parabiosis [33].…”
Section: Discussionmentioning
confidence: 90%
“…No considerable changes in the expression level of the IκBα protein in activated T-cells from different experimental groups were marked in this stage of activation. However, the level of the activated form of caspase 3 (p20) was still considerably higher in T-cells from young isochronic and young heterochronic parabionts in comparison with T-cells from either old isochronic or heterochronic parabiotic animals [33].…”
Section: The Study Of Age-related Changes Of Lymphoid Niche Cells In mentioning
confidence: 89%
“…in the case of impaired Schwann cell function [17], impaired T cell subset distribution [18], function [19] and thymic involution [18,20], and in the first two examples pro-geronic effects were noted in the adult animal. Regarding individual pro-geronic molecules, increased levels of CCL11 and b2m with age are associated with decreased brain functions [8,11] and increased b-catenin signalling was implicated in defects in bone repair [14].…”
Section: Heterochronic Parabiosis As Means To Study Ageing and (Immunmentioning
confidence: 99%
“…With regard to ageing of the immune system, Pishel et al published observations of accelerated ageing of the immune system as determined by the failure to restore thymic mass of the old animal and an increase of CD44 1 memory T cells in the young animal and diminished T cell proliferation and T cell receptor (TCR) signalling upon invitro stimulation [18,19]. These studies did not use congenic markers to distinguish between adult and old T cells in critical experiments, and conducted bulk T cell assays that do not account for the different proportions of T cell subsets with age.…”
Section: Heterochronic Parabiosis As Means To Study Ageing and (Immunmentioning
confidence: 99%
“…These changes were expressed by a decrease in the CD4/CD8 ratio, and an increase in the number of CD8+44+ and CD4+44+ memory cells in the spleen. The study of the mechanism of such rapid age-related changes in the immune system of young heterochronous partners showed that it may be associated with thymus atrophy [83], or disturbance in exposure to "aged" antigenpresenting cells of the microenvironment of lymphoid organs [84][85][86], or a paradoxical decrease in regulatory FoxP3+CD4+25+ T cells in old partners [83]. It is known that a decrease in the number of Tregs can lead to homeostatic T cell proliferation [87,88].…”
Section: Systemic Blood and Cells Exchange In Heterochronic Parabiosismentioning
confidence: 99%